Genotoxicity studies of substance-P by using short-term assay - Hong, Hyun Sook; Yim, Sung-Vin; Son, Youngsook (Molecular & cellular toxicology, 2016)
Substance-P (SP) can function of mobilizing mesenchymal stem cells (MSCs) from the bone marrow to the circulation and exert anti-inflammatory effects by increasing anti-inflammatory M2-type macrophage and regulatory T cells in the circulation. The preclinical efficacy of SP was demonstrated in a variety of conditions including ischemia damages, but its safety was not assessed. In this study, we assessed the genotoxicity of SP by using in vitro bacterial reverse mutation assay, chromosomal aberration assay, and in vivo micronucleus test. The maximum test dose of SP was 250 μg/mL in a cell-based assay and 16.6 mg/kg for an in vivo test. Ames test revealed SP did not increase in the number of revertant colonies. An in vitro chromosomal aberration assay with Chinese hamster lung cells showed that SP was not clastogenic even at the maximum dose applied. In vivo micronucleus test also demonstrated that SP did not induce micronuclei formation in the bone marrow cells of male ICR mice. Taken together, our results suggest that SP is not mutagenic to bacterial cells. Moreover, SP does not cause chromosomal damage in mammalian cells either in vitro or in vivo .